2023
DOI: 10.1002/aenm.202203751
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Energy Carriers: Unique Interfaces for Electrochemical Hydrogenic Transformations

Abstract: The shift toward renewable energy generation sources, characterized by their non‐carbon emitting but variable nature, has spurred significant innovation in energy storage technologies. Advancements in foundational understanding from investments in basic science and clever engineering solutions, coupled with increasing industrial adoption, have resulted in a notable reduction in the cost of storing electricity from variable energy generation sources. These developments have paved the way for the exploration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 161 publications
0
9
0
Order By: Relevance
“…The Helmholtz model led to the concept of a "double layer" of charged species, but it significantly overpredicts the magnitude of interfacial capacitances and neglects the essential role of entropy in governing molecular level details of electric field screening. 7 By the early 1900s the double layer concept proposed by Helmholtz was being refined in parallel with expanding interest in statistical thermodynamics. It was found that "de-mixing" a bulk electrolyte into a single layer of charge-compensating ions would incur an entropic penalty that would outweigh the energetic stabilization offered by electrostatic screening.…”
Section: Theoretical Understanding Of Electric Double Layersmentioning
confidence: 99%
See 2 more Smart Citations
“…The Helmholtz model led to the concept of a "double layer" of charged species, but it significantly overpredicts the magnitude of interfacial capacitances and neglects the essential role of entropy in governing molecular level details of electric field screening. 7 By the early 1900s the double layer concept proposed by Helmholtz was being refined in parallel with expanding interest in statistical thermodynamics. It was found that "de-mixing" a bulk electrolyte into a single layer of charge-compensating ions would incur an entropic penalty that would outweigh the energetic stabilization offered by electrostatic screening.…”
Section: Theoretical Understanding Of Electric Double Layersmentioning
confidence: 99%
“…In this model, the separation distance between the charged planes and the total charge density of the planes defines the interfacial capacitance, which is proportional to the electrochemical energy stored at the polarized interface. The Helmholtz model led to the concept of a “double layer” of charged species, but it significantly overpredicts the magnitude of interfacial capacitances and neglects the essential role of entropy in governing molecular level details of electric field screening …”
Section: Theoretical Understanding Of Electric Double Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…The depletion of fossil fuels has become a pressing issue that necessitates collective action by human society. The development and implementation of renewable, clean energy are considered the most direct and effective approach to tackling this problem. , Hydrogen, with its exceptionally high combustion calorific value and absence of combustion byproducts that damage the environment, is regarded as one of the best clean energy sources. Water electrolysis has been considered an efficient technique for hydrogen production, but the oxygen evolution reaction (OER) at the anode with a complex four-electron transfer process has posed a bottleneck in the overall water-splitting process. Although commercial IrO 2 and RuO 2 are excellent catalysts for OER, their high cost and limited natural reserves have restricted their widespread use. Consequently, researchers have progressively investigated the development and use of highly efficient, stable, and inexpensive OER catalysts for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, as the world races against time to achieve the 2050 carbon neutrality target, the drive for efficient energy utilization has been significantly intensified, taking into consideration the fact that resource extraction has more than tripled since 1970, which includes a 45% increase in fossil fuel use . Increasing efforts are being directed toward innovation in the utilization and transformation of energy, such as a substantial reduction in fossil fuel use, the adoption of low-emission energy sources, the transition to alternative energy carriers, and the implementation of measures to improve energy efficiency and promote conservation. That is, clean, low-cost, highly efficient, and sustainable energy production is thus in urgent demand. Notably, hydrogen, a carbon-free molecule with the highest energy content per mass unit and calorific value, , has stood out and garnered widespread attention as a sustainable and environmental-friendly energy source across various sectors, ranging from industry to transportation. , A viable option for harnessing renewable, cost-free, and clean solar energy is the usage of photocatalytic technology, i.e., water splitting driven by sunlight into its elemental components (H 2 and O 2 ) without any additional energy input becomes the cornerstone of sustainable energy sources. , Although several breakthroughs have been made since the pioneering work in semiconducting oxides (like TiO 2 ), overpowering recombination of photogenerated carriers and the limited utilization rate of solar energy result in the low availability of nontoxic and highly efficient catalysts with a high photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%